Extending a social control framework to explain the link between romantic relationships and violent victimization by non-intimate perpetrators: a study of actor and partner effects - Schreck, Christopher J. (Justice quarterly, 2024)
Victim data reveals that romantic relationships correspond to significant reductions in violent victimizations committed by strangers and acquaintances. This study offers a more detailed exploration of this finding. Specifically, we investigate the effect of relationship quality and structure on victimization risk in combination with mechanisms a social control perspective would suggest as theoretically possible. We also consider the independent contributions of both romantic partners toward this apparent protective effect. We use two waves of adult data from the National Longitudinal Study of Adolescent Health, which include data from both respondent and their partner and adjust for treatment selection a series of models. The protective benefits of relationship quality for the individual respondent appeared to have: (1) functioned irrespective of their partner’s perception of relationship quality, (2) were negated or related to even greater victimization risk if the relationship quality was poor, and (3) were explained by reductions in lifestyle choices associated with risk of violent victimization.